2019
DOI: 10.1111/codi.14870
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial comparing transanal irrigation and percutaneous tibial nerve stimulation in the management of low anterior resection syndrome

Abstract: Aim To assess the effectiveness of transanal irrigation (TAI) compared with posterior tibial nerve stimulation (PTNS) in severe and chronic low anterior resection syndrome (LARS). Method A two‐group parallel, open‐label randomized controlled trial carried out in a single university hospital. The study population included patients with a LARS scale score of more than 29 points who had undergone rectal surgery more than 1 year previously. These were randomly allocated, with a central randomization system, fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 14 publications
0
31
0
1
Order By: Relevance
“…In total, seven studies were identified reporting data on the effect of TAI in patients with LARS [38][39][40][41][42][43][44]. Results are presented in Table 2.…”
Section: Low Anterior Resection Syndromementioning
confidence: 99%
See 3 more Smart Citations
“…In total, seven studies were identified reporting data on the effect of TAI in patients with LARS [38][39][40][41][42][43][44]. Results are presented in Table 2.…”
Section: Low Anterior Resection Syndromementioning
confidence: 99%
“…The articles were published between 1989 and 2020. Five studies investigated TAI as a treatment for LARS [38][39][40][41][42], and two studies investigated TAI as a prophylactic treatment for LARS immediately after ileostomy closure [43,44].…”
Section: Low Anterior Resection Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that LAR and especially ISR often lead to severe functional problems both in short and long term and may result in a poor defecatory function. Patients with very low anastomoses are especially prone to develop a condition termed "low anterior resection syndrome" [18], which incorporates a number of unpleasant symptoms such as frequent defecation, urgency, and stool incontinence, and severely impairs QoL. These commonly occurring problems after deep sphincterpreserving surgery are probably the reason why recent studies have shown that QoL after ISR and LAR, contrary to former beliefs, is not better than QoL after APR.…”
Section: Discussionmentioning
confidence: 99%